Total dose infusion of fractionated iron dextran complex in management of anaemia in antenatal cases - S, Manjunath; H C, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Iron deficiency anemia is common clinical manifestation in pregnancy. It can be easily prevented or corrected by early diagnosis and proper treatment successfully. This study was done to know the efficacy, effectiveness, rise in hemoglobin level and adverse effects of newly available low molecular weight iron dextran complex. Methods: A prospective clinical trial was conducted in randomly selected 50 antenatal women who attended the OPD of OBG department and were moderately anemic and fulfilled the inclusion criteria of the study Results: All the 50 women were moderately anemic with hemoglobin level between 7-9 gm%. After total dose infusion of low molecular weight fractionated iron dextran complex, hemoglobin level was measured at 4 weeks and at term. The mean hemoglobin level rose to 9.5 gm/dl by 4 weeks after infusion and to 11.53 gm/dl at term, which was statistically significant (p<0.0001). Only one patient developed non-cardiac chest pain during the test dose and two patients developed urticaria during total dose infusion. Conclusion: The study showed a statistically significant increase in hemoglobin level after total dose infusion of low molecular weight iron dextran complex with a good safety profile and minimal hospital stay.